Long-Term Return to Work After Acquired Brain Injury in Young Danish Adults: A Nation-Wide Registry-Based Cohort Study - Tibæk, Maiken; Kammersgaard, Lars Peter; Johnsen, Søren P.; Dehlendorff, Christian; Forchhammer, Hysse B. (Frontiers in Neurology, 2019)
Abstract Objective: (1) To determine patterns of return to work (RTW) after traumatic brain injury and other causes of acquired brain injury (ABI) among young adults aged 19-30 years and (2) to compare the stability of long-term labor-market attachment (LMA) to the background population. Method: Nationwide registry-based inception cohort study of 10 years weekly data of employment status. Patients (n=8,496) aged 19-30 years with first-ever diagnosis of TBI, stroke, subarachnoid hemorrhage, encephalopathy, brain tumor or CNS infections during 1999-2015. For comparison, a general population cohort (n=206,025) individually matched on age, sex and municipality was identified. The main outcome was RTW, which was defined as time to LMA, i.e. a week without public assistance benefits except education grants/leave. Stable labor-market attachment (sLMA) was defined as LMA for at least 75% over 52 weeks. The cumulative incidence proportions of RTW and stable RTW in the ABI cohort were estimated with the Aalen-Johansen estimator with death as a competing event. Results: Twelve weeks after diagnosis 46.9% of ABI cohort had returned to stable RTW, which increased to 57.4% one year after, and 69.7% ten years after. However, compared to controls fewer had sLMA one year (OR: 0.25 [95% CI 0.24-0.27]) and ten years after diagnosis (OR: 0.35 [95% CI: 0.33-0.38]). Despite significant variations, sLMA was lower compared to the control cohort for all subtypes of ABI and no significant improvements were seen after 2-5 years. Conclusion: Despite relatively fast RTW only a minor proportion of young patients with ABI achieves sLMA. Key words: Brain Injury, return to work, employment, prognosis, TBI, yung adults